Interferon modulation of c-myc expression in cloned Daudi cells: relationship to the phenotype of interferon resistance. - Dron, M (1986)
Treatment of interferon-sensitive Daudi cell with electrophoretically pure human interferon alpha markedly reduced the level of c-myc mRNA, increased the level of class I histocompatibility antigen (HLA) mRNA, and did not affect the level of actin mRNA within the same cells. In contrast, the level of c-myc mRNA or HLA mRNA did not change significantly following interferon treatment in different clones of Daudi cells selected for resistance to the antiproliferative action of interferon. These cells possessed interferon receptors, however, and responded to interferon modulation of other genes, including 2',5' oligoisoadenylate synthetase (M. G. Tovey, M. Dron, K. E. Mogensen, B. Lebleu, N. Metchi, and J. Begon-Lours, Guymarho, J. Gen. Virol., 64:2649-2653, 1983; M. Dron, M. G. Tovey, and P. Eid, J. Gen. Virol., 66:787-795, 1985). A clone of interferon-resistant Daudi cells which had reverted to almost complete sensitivity to both the antiproliferative action of interferon and the interferon-enhanced expression of HLA mRNA remained refractory, however, to interferon modulation of c-myc expression, suggesting that a reduced level of c-myc mRNA may not be a prerequisite for inhibition of cell proliferation in interferon-treated cells. Our results do not exclude the possibility, however, that posttranscriptional modification(s) of c-myc expression may precede an inhibition of cell proliferation in interferon-treated cells.